Mimickers of Hill-Sachs Lesions. Issue 2 (May 2021) - Herring, Allison; Davis, Derik L.
The purpose of this article is to describe the imaging appearance, etiology, clinical features, and treatment of rare presentations of common bone and joint diseases known to mimic Hill-Sachs lesions. Knowledge of uncommonly encountered manifestations of ankylosing spondylitis, rheumatoid arthritis, septic joint, hyperparathyroidism, hydroxyapatite deposition disease, malignant bone tumors, and benign bone cysts which mimic traumatic Hill-Sachs lesions is important for radiologists to guide the clinical care of patients who present with shoulder symptoms.